PERAN KINERJA KEUANGAN SEBAGAI PEMODERASI PENGUNGKAPAN SUSTAINABILITY REPORTING DAN INTANGIBLE ASSETS TERHADAP NILAI PERUSAHAAN - Sari Rahmadhani; Noor Salim (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to examine the impact on financial performance of sustainability reporting factors and intangible assets that can influence company value in the post-Covid 19 pandemic. The sample in this research is 49 companies that are listed on the Indonesia Stock Exchange and submitted good sustainability reports from 2019 to by 2021. By applying Moderated Regression Analysis (MRA), the results show that financial performance strengthens the influence of sustainability reports on company value. Likewise, financial performance strengthens the influence of intangible assets on company value. High financial performance plays an important role in strengthening sustainability reporting and intangible assets so that they increase or decrease in line with firm value. The results of this research contribute to companies to transparently disclose conditions in sustainability reports and intangible assets can interact with the company's financial performance to increase company value, especially external factors beyond control that are less supportive.